2013
DOI: 10.4254/wjh.v5.i10.584
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for liver fibrosis among human immunodeficiency virus monoinfected patients using the FIB4 index in Morocco

Abstract: AIM:To study the prevalence and risk factors of significant hepatic fibrosis in Moroccan human immunodeficiency virus (HIV) monoinfected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
1
10
1
Order By: Relevance
“…This is consistent with a large case–control study performed in Uganda (where hepatitis co‐infection and heavy alcohol use was uncommon), which showed that HIV infection was linked to increased risk of liver fibrosis . Also, high plasma HIV RNA level has been shown in other studies to correlate with degree of liver fibrosis in both ART‐treated and ART‐naïve individuals . These data suggest that HIV infection per se may have a role in the pathogenesis of liver fibrosis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with a large case–control study performed in Uganda (where hepatitis co‐infection and heavy alcohol use was uncommon), which showed that HIV infection was linked to increased risk of liver fibrosis . Also, high plasma HIV RNA level has been shown in other studies to correlate with degree of liver fibrosis in both ART‐treated and ART‐naïve individuals . These data suggest that HIV infection per se may have a role in the pathogenesis of liver fibrosis.…”
Section: Discussionsupporting
confidence: 89%
“…The burden of liver fibrosis in HIV‐infected individuals had not been fully evaluated in the absence of hepatitis co‐infection . Recent research showed that 8–15% of HIV‐monoinfected individuals (hepatitis B and C excluded) had significant liver fibrosis . Most of these studies, however, had used serum biomarkers and/or clinical prediction formulae for estimation, which might have sub‐optimal performance in HIV‐infected individuals .…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study of 432 HIV-positive individuals (without HBV or HCV infection), significant fibrosis as determined by APRI was found in 8% of patients [24]. In another study, again in HIV-monoinfected individuals but this time using FIB-4, a score of > 1.45 (consistent with significant fibrosis) was found in 15.5% of individuals [23]. In our study based on elastography assessment, the prevalence of significant fibrosis (TE > 7.2 kPa indicating F2 and above) in untreated HIV-positive individuals was 7.8%.…”
Section: Discussionmentioning
confidence: 96%
“…These findings suggest the requirement of a monitoring of this serum marker over time in the HIV-infected population, independently from HCV serostatus. Altogether these observations on the prognostic value of baseline and time-updated FIB-4 in HIV suggest that this as a relevant marker that can be employed for prospective interventional studies both in the HCV co-infected population, where it might be used to prioritize the newer treatment options with directly acting antivirals, as well as in the HCV negatives where it might be used for other specific interventions aimed at reducing the risk of fibrosis evolution, by acting on modifiable factors such as the control of diabetes and, in particular, stopping alcohol use and increasing the CD4 counts, which may best be obtained by an early ART initiation [ 23 , 25 ].…”
Section: Discussionmentioning
confidence: 99%